1D Chains of Diruthenium Tetracarbonyl Sawhorse Complexes. Issue 1 (3rd January 2018) - Fritsch, Nico; Wick, Christian R.; Waidmann, Thomas; Pflock, Stephan; Dral, Pavlo O.; Tucher, Johannes; Steiner, Christian; Shubina, Tatyana E.; Maier, Sabine; Clark, Timothy; Burzlaff, Nicolai
Abstract : The syntheses of five 1D coordination polymers containing the sawhorse‐type unit [Ru2 (µ‐OAc)2 (CO)4 ] linked by various bridging N, N‐donor ligands are reported. Various π‐conjugated linkers, such as trans ‐[1, 2‐bis( N ‐methyl)imidazol‐2‐yl]ethylene ( trans ‐bie), pyrazine (pyz), 4, 4′‐bipyridine (4, 4′‐bipy) and 1, 2‐bis(4‐pyridyl)ethylene (bpe) as well as the aliphatic linker 1, 4‐diazabicyclo[2.2.2]octane (DABCO), were applied in the syntheses. The formation of 1D coordination polymers was proven by crystal structure determinations of two of the polymeric materials. The geometries and electronic structures of all polymers were analysed further by CASSCF/CASPT2 and DFT calculations based on monomeric model compounds. Finally, first attempts regarding deposition of the 1D chain, the sawhorse fragment and/or the ligands on a highly ordered pyrolytic graphite surface, analysed by STM measurements, are also reported. Abstract : 1D coordination polymer chains are formed by linking [Ru2 (µ‐OAc)2 (CO)4 ] sawhorse units by bridging N, N ligands. Bond orders were analysed by means of CASSCF/CASPT2 and DFT calculations.